PERUMUSAN PEDOMAN INTERNALISASI NILAI-NILAI BUDAYA PERUSAHAAN DI PABRIK ROKOK SUKUN PUSAT - Tuti Ningrum; Fera Elviana (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
Culture has an important role in the company. One of the elements in corporate culture is values. Companies must ensure that the culture is acceptable and even practiced by employees. PR Sukun it self has problems related to employees' understanding of their cultural values. Internalization can be used as one of the company's strategies to ensure that cultural values ​​can be accepted and implemented. Of course, guidelines are needed as the basis for the implementation of internalization. Purpose of this study is to know the guidelines formulation process for the internalization of corporate cultural values. This research uses descriptive-qualitative. Data collected by triangulation method that are interviews, documentation, and observation. The results show that PR Sukun had espoused values “Sukun Kuat”, that are (contibutive, strong, original, and tados). Moreover, this research also got information about conditions and steps for internalizing the current PR Sukun values. The results are compared with the references obtained by the writer to make recommendation. The recommendations of this guideline contain the preparation of guide or internalization materials, the formation of agents of change and their duties, planning of internalization programs, and monitoring evaluations.